QUALITY OF LIFE IN PEDIATRIC PATIENTS WITH EPILEPSY ON ANTIEPILEPTIC DRUGS: A CROSS-SECTIONAL STUDY USING QOLCE-55 TOOL IN NORTH INDIA - Mehta, Kanav; Kumar, RAJ; Kaur, Navreet (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective of this study is to assess the impact of epilepsy and antiepileptic medication on the quality of life (QoL) of children with epilepsy, particularly in the northern region of India. Methods: This was a cross-sectional, hospital-based study that collected social demographic and clinical data from 100 children aged between ≥4 and ≤14 years. QoL was assessed using the QoL in Children with Epilepsy (QOLCE-55) questionnaire. Results: The mean total QOLCE-55 score was 58.66±22.02, with the physical domain being the most affected. Age, seizure frequency in the last year, and schooling status showed significant associations with the mean QOLCE-55 score. However, there were no significant associations observed with gender, area of residence, socioeconomic status, type of epilepsy, type of antiepileptic drug, and family history of epilepsy. Significance: The study emphasizes the significance of health-care providers focusing on the physical well-being of children with epilepsy, especially in resource-constrained developing countries, particularly in their rural areas. Age, seizure frequency, and schooling status showed significant associations with the QOLCE. These factors should be taken into account while designing treatment plans to ensure effective and equitable health care interventions.